2022
DOI: 10.1186/s12889-022-14006-x
|View full text |Cite
|
Sign up to set email alerts
|

Health care utilization among individuals who die by suicide as compared to the general population: a population-based register study in Sweden

Abstract: Background Globally, 700 000 people die every year by suicide. Health care consultation patterns the period before suicide could be one potential way to identify people at risk for suicide. Therefore, this study examines health care patterns up to one year prior to the suicide by age, sex and prior diagnoses and specifically investigates if and how this differs from the general population of Skåne, Sweden. Methods This cohort study includes all ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 43 publications
1
3
0
Order By: Relevance
“…Additionally, Long COVID is commonly reported by individuals who were not hospitalized during the acute phase of COVID-19 4 . Thus, Long COVID became a global public health issue due to its high prevalence and association with several adverse health-related outcomes, such as rehospitalization and mortality [5][6][7] . Individuals with Long COVID may experience several concurrent adverse physical symptoms, including fatigue, dyspnea, post-exertional malaise, and myalgia 3 , making the rehabilitation process extremally challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Long COVID is commonly reported by individuals who were not hospitalized during the acute phase of COVID-19 4 . Thus, Long COVID became a global public health issue due to its high prevalence and association with several adverse health-related outcomes, such as rehospitalization and mortality [5][6][7] . Individuals with Long COVID may experience several concurrent adverse physical symptoms, including fatigue, dyspnea, post-exertional malaise, and myalgia 3 , making the rehabilitation process extremally challenging.…”
Section: Introductionmentioning
confidence: 99%
“…However, evidence shows that many existing clinical training programmes do not adequately prepare healthcare professionals to engage in suicide prevention (4,5). A population-based cohort study conducted in Sweden between 2004 and 2015 found that 86% of individuals who died by suicide received healthcare in the year preceding their death (6). It was also estimated that in the month before their death, 53% of those who died by suicide had received some form of healthcare consultation.…”
Section: Introductionmentioning
confidence: 99%
“…It was also estimated that in the month before their death, 53% of those who died by suicide had received some form of healthcare consultation. This is compared with 20% in the general population (6). Health professionals, such as nurses, pharmacists, primary care providers and social workers, are well-positioned to detect signs and symptoms of suicidal ideation and behaviours and provide those at risk with the appropriate referrals to support (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%
“…A population-based cohort study conducted in Sweden between 2004 and 2015 found that 86% of individuals who died by suicide received healthcare in the year preceding their death [7]. It was also estimated that in the month before their death, 53% of those who died by suicide had received some form of healthcare consultation.…”
Section: Introductionmentioning
confidence: 99%
“…It was also estimated that in the month before their death, 53% of those who died by suicide had received some form of healthcare consultation. This is compared with 20% in the general population [7]. Health professionals, such as nurses, pharmacists, primary care providers and social workers, are well-positioned to detect signs and symptoms of suicidal ideation and behaviours and provide those at risk with the appropriate referrals to support [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%